Relationship of Self Efficacy with Self Care Management in Pregnant Women Approaching Childbirth - Rita Aninora, Novia; Wikarya, Rionitara; Permata Sari, Putri (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: The process of pregnancy and childbirth, is estimated to be 85% normal and only 15% experience complications. Pregnant women with high self-efficacy are more confident in managing blood pressure, following the recommended diet, and complying with routine health check-up schedules, on the other hand pregnant women with low self-efficacy will experience stress, give up easily and do not believe in their abilities. Objective: The aim of this study was to determine the relationship between self-efficacy and self-care management in pregnant women approaching childbirth. Method: This study uses a quantitative research design with a cross-sectional approach. The population in this study were pregnant women in the third trimester. The sampling technique used purposive sampling with a total of 37 people. Data were collected through questionnaires. Data analysis was done univariately and bivariate using the chi-square test. Result and Discussion: Less than half of respondents (37.8%) Self-Care Management is lacking, more than half (62.2%) self-efficacy is certain, there is a relationship between Self Efficacy and Self Care Management in pregnant women approaching pregnancy at the Alai Health Center, Padang City in 2025 Conclusions: Self-efficacy plays an important role in self-care management in pregnant women approaching childbirth. Increasing self-efficacy can be an effective strategy to support maternal and infant health.